2017
DOI: 10.1177/1073191116689819
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Assessment of the Negative Emotion Aspect of Distress Tolerance: Tolerance to Emotional Images

Abstract: The current behavioral tasks assessing distress tolerance measure tolerance to frustration and tolerance to physical discomfort, but do not explicitly assess tolerance to negative emotion. We closely evaluated the conceptual distinctions between current behavioral tasks and self-report tasks assessing distress tolerance, and then developed a new behavioral distress tolerance task called the Emotional Image Tolerance (EIT) task. The EIT task retains elements of existing behavioral tasks (e.g., indices of persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 52 publications
4
40
0
Order By: Relevance
“…Additionally, despite the overwhelming amount of evidence to suggest that self-reported DT is negatively related to depression, the relation between depression and DT tasks is much less straightforward. Studies that have compared depressed to nondepressed individuals have found significant differences in DT (Ameral et al, 2017;Ellis et al, 2010Ellis et al, , 2013), but when examining task performance and depressive symptoms continuously, the results are mixed (Anestis et al, 2012;Bernstein et al, 2011;Cummings et al, 2013;Doan et al, 2018;Gorka et al, 2012;Iverson et al, 2012;Kiselica et al, 2015;Veilleux et al, 2019). Only relatively few studies have examined these differences, and they vary greatly in their designs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, despite the overwhelming amount of evidence to suggest that self-reported DT is negatively related to depression, the relation between depression and DT tasks is much less straightforward. Studies that have compared depressed to nondepressed individuals have found significant differences in DT (Ameral et al, 2017;Ellis et al, 2010Ellis et al, , 2013), but when examining task performance and depressive symptoms continuously, the results are mixed (Anestis et al, 2012;Bernstein et al, 2011;Cummings et al, 2013;Doan et al, 2018;Gorka et al, 2012;Iverson et al, 2012;Kiselica et al, 2015;Veilleux et al, 2019). Only relatively few studies have examined these differences, and they vary greatly in their designs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this finding is discriminant, such that the difference emerges in response to anger but not to anxiety or sadness (Ellis et al, 2010); however, examining behavioral DT tasks and depressive symptoms measured continuously (as opposed to looking at depressed versus nondepressed) yields mixed results. Two studies have found a negative relationship between behavioral tasks of DT and symptoms of depression (Doan, Son, & Kim, 2018;Gorka, Ali, & Daughters, 2012), but the majority of studies examining depressive symptoms and performance on DT tasks found no differences (Anestis et al, 2012;Bernstein et al, 2011;Cummings et al, 2013;Iverson et al, 2012;Kiselica et al, 2015;Veilleux et al, 2019).…”
Section: Behavioral Measures Of Dtmentioning
confidence: 99%
“…Several tasks have been developed and used to index behavioral DI, including persistence during exposure to thermal pain (Neufeld & Thomas, 1977; Rhudy & Meagher, 2003) or respiratory distress (Brown, Lejuez, Kahler, & Strong, 2002; Hajek, Belcher, & Stapleton, 1987; Marshall et al, 2008). Exposure to stressful/frustrating mental tasks (Lejuez, Kahler, & Brown, 2003; Quinn, Brandon, & Copeland, 1996; Strong et al, 2003) or to negative emotional pictures (Veilleux, Pollert, Zielinski, Shaver, & Hill, 2017) are used to measure intolerance for mental and emotional distress, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These two conceptualizations are reflected in the ways in which distress tolerance is broadly assessed, which involves both selfreport measures as well as behavioral/biobehavioral measures (Zvolensky, Vujanovic, Bernstein, & Leyro, 2010). Although self-report measures exist for all five dimensions, researchers have had difficulty creating reliable behavioral measures that specifically assess EDT (Veilleux, Pollert, Zielinski, Shaver, & Hill, 2019), which may be the most relevant facet of distress tolerance to anxiety.…”
Section: Distress Tolerance Definition and Measurementmentioning
confidence: 99%
“…Since the DTS includes items related to one's judgment of the experience of distress (Veilleux et al, 2019), it may be helpful to identify for any given patient whether the more "important" aspect of EDT for them personally is their willingness to continue engaging in treatment despite their distress (i.e. the behavioral component), or their judgments of their Note.…”
Section: Future Directionsmentioning
confidence: 99%